ANALISIS UNJUK KERJA PEMBANGKIT LISTRIK TENAGA SURYA (PLTS) ATAP ON-GRID 463,25 kWp DI PERUSAHAAN FARMASI PADA KAWASAN PT JAKARTA INDUSTRIAL ESTATE PULOGADUNG, JAKARTA TIMUR - Neysa Amelia Hutagalung; I Nyoman Setiawan; I Wayan Sukerayasa (Jurnal SPEKTRUM, 2023)
The number of PLTS installed on factory rooftops is growing. In Indonesia, the Directorate General of New, Renewable Energy estimates a total renewable energy potential of 442 GW, with solar energy holding the greatest potential. The performance of the PLTS system needs to be considered to ensure good performance in generating electricity. This research focuses on the rooftop on-grid PLTS system in a Pharmaceutical Company located in the PT Jakarta Industrial Estate Pulo Gadung area, with a capacity of 463.25 kWp. Electricity generation potential is modeled using PVSyst software for examination of the PLTS system's performance. For the period of one year, from November 2021 through October 2022, the PLTS system's performance characteristics are determined. These include the Yield Factor (Yf), Reference Yield (Yr), Performance Ratio (PR), and Capacity Utilization Factor (CUF). According to the model, the 463.25 kWp on-grid rooftop PLTS system may generate up to 629,550 kWh of power each year. The values of the PLTS system performance parameters are as follows: Yield Factor (Yf) is 1,358.99 kWh/kWp, Reference Yield (Yr) is 1,730.6 kWh/kW, Performance Ratio (PR) is 78.56%, and Capacity Utilization Factor (CUF) is 15.73%. Meanwhile, the actual electricity production for one year is 570,724.82 kWh, with the following performance parameters for the PLTS system: Yield Factor (Yf) is 1,232 kWh/kWp, Reference Yield (Yr) is 1,642.85 kWh/kW, Performance Ratio (PR) is 76.12%, and Capacity Utilization Factor (CUF) is 14.26%. There is a difference between the PVSyst software simulation and the actual results, which are 58,825.18 kWh, 126.98 kWh/kWp, 87.75 kWh/kW, 2.44%, and 1.47% respectively.